Field notes contributed by Tanya Bray, winter 1983-1984 - Bray, Tanyaet al (1983)
Field notes were contributed by Tanya Bray, winter 1983-1984. Other observers were Don Bray, Babs Padelford, and Sandra Kovanda. A detailed description was given of two Greater Scaup drakes seen at the IPL Ponds near Council Bluffs. The other birds reported were a Northern Harrier at Lake Manawa, two Gray Partridges by I-29 in Harrison County, a Greater Prairie-Chicken at the De Soto NWR, 1400 Snow Geese at Forneys Lake, and a Peregrine Falcon at De Soto Bend. A February 27 cover letter to Thomas H. Kent mentioned three Gyrfalcon sightings in Nebraska. These items were used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed/flatbed